PENGARUH JUMLAH PENDUDUK, PRODUK DOMESTIK BRUTO DAN TENAGA KERJA KEHUTANAN TERHADAP LUAS KEBAKARAN HUTAN DAN LAHAN DI INDONESIA - Erwinsyah - - (Populis : Jurnal Sosial dan Humaniora, 2017)
This research was purposed to develop model of impact caused by population, affluence, and technology, IPAT, to predict the effect of population total, Gross Domestic Producs (GDP) per Capita, and  forestry emplotee on forests and lands fire in Indonesia. This research was pointed out that additional of pupulation gives very siginificant effect, GDP Per Capita and forestry employee each gives significant effect to the total areas of forests and lands fire at nine provinces in Indonesia, namely North Sumatra, Riau, Jambi, South Sumatra, West Kalimantan, East Kalimantan, Central Kalimantan, South Kalimantan and Papua. This result was proven that IPAT model can be used to understand about anthropogenci factors contribute to the forests and lands fire in Indonesia.